In vitro and in vivo Activity of Phibilin Against Candida albicans - Li, Zhongjie; Jing, Xiaoyuan; Yuan, Yaping; Shui, Yingbin; Li, Shasha; Zhao, Zhuoran; Deng, Bo; Zhang, Wenlu (Frontiers in Microbiology, 2022)
The increase in the occurrence of antifungal resistant Candida albicans infections necessitates more research to explore alternative effective and safe agents against this fungus. In this work, Phibilin, a new antimicrobial peptide from the traditional Chinese medicine Philomycus bilineatus, effectively inhibits the growth and activities of C. albicans including the clinical resistant strains. As a fungicidal antimicrobial peptide, Phibilin exerted its antimicrobial effect against C. albicans mainly by disrupting the membrane and interacting with the DNA of the fungi. In particular, Phibilin induces necrosis of C. albicans via the ROS-related pathway. Moreover, Phibilin inhibited the biofilm formation of C. albicans by preventing hyphal development in a dose-dependent manner. Furthermore, Phibilin and Clotrimazole displayed a synergistic effect in inhibiting the growth of the fungi. In the mouse cutaneous infection model, Phibilin significantly inhibited the formation of skin abscesses and decreased the counts of C. albicans cells in the infection area. Overall, Phibilin is potentially an effective agent against skin infections caused by C. albicans.